SIKAP DAN PERILAKU SEKSUAL TOKOH PEREMPUAN DALAM NOVEL SAMAN KARYA AYU UTAMI - Faisal Faisal; Hajrah Hajrah; Fenny Juniza Fabiola (Universitas Negeri Makassar, 2023)
Attitudes and Sexual Behavior of Female Characters in Ayu Utami's Saman Novel. This study aims to describe the forms of attitudes and sexual behavior of female characters and what factors cause them in the novel, which is used as a source of data analyzed. This study uses a qualitative descriptive method that consists of four analytical techniques: word reduction, categorization, data presentation, and data inference. The source of the research data is the novel Saman by Ayu Utami. The material used in this research is text, sentences, and paragraphs that reveal and describe the sexual attitudes and behaviors of female characters as well as the causative factors in Ayu Utami's novel Saman by using Sigmund's theory of sex. The results of this study indicate that, first, the novel character Saman experiences various types of sexuality, such as hermaphrodite, fanaticism, eroticism, promiscuity, infidelity, and adultery. Second, the factors causing the sexual orientation of the characters in the novel Saman are varied, including sexual dysfunction, social interest, frustration with requests that cannot be achieved, and a lack of brains.